GERARD OF CREMONA: THE DANGER OF BEING HALF-ACCULTURATED. - Weber, Michael C. (Medieval Encounters, 2002)
This article calls for a nuanced reappraisal of the talents of Gerard of Cremona, the most prolific of the so-called "Toledan Translators" of the twelfth century. By carefully examining his translation of a wide-ranging text of al-Farabi and comparing it with the translation made by Dominicus Gundisalvus a tentative evaluation of his knowledge of specific content areas, of Islamic culture, and his skill and practices as a translator is put forth as a contribution to the increasingly sophisticated understanding of this important epoch in medieval intellectual history.